HUBUNGAN PERILAKU KESEHATAN GIGI DAN MULUT TERHADAP PENCEGAHAN KARIES GIGI PADA ANAK SD SWASTA KARTIKA 1-1 MEDAN - Mulidan Mulidan; Yuniati, Dian Kasih Putri Halawa (CV. ADIBA AISHA AMIRA, 2022)
Dental and oral health is very important because it can affect the health of other body parts, where the oral cavity is the main route or entrance for microorganisms. The behavior of maintaining dental and oral hygiene should be instilled from an early age. Behavior is the result of all kinds of experiences and interactions between humans and their environment. The form of behavior can be in the form of knowledge, attitudes, and actions. This study aimed to determine the relationship between dental and oral hygiene behavior on the prevention of dental caries in students of SD Swasta Kartika 1-1 Medan. This is an analytical survey research with a cross sectional approach. The population in this study was students of SD Swasta Kartika 1-1 Medan as many as 250 people. The sampling technique used purposive sampling with Slovin formula as many as 71 respondents. The data collection instrument used a questionnaire which was distributed directly to the respondents. Data were analyzed using univariate and bivariate analysis using and tested by chi-square test. The results of the study based on the chi-square test on the relationship of oral health behavior to the prevention of dental caries obtained in the high knowledge category with p-value = 0.004, the positive attitude category with p-value = 0.003, and the action category with p-value = 0.004. The conclusion shows that there is a significant relationship between knowledge, attitudes, and actions towards the prevention of dental caries in students of SD Swasta Kartika 1-1 Medan